2007
DOI: 10.1902/jop.2007.060062
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Atherosclerosis and Periodontal Putative Pathogenic Bacterial Infections in Coronary and Internal Mammary Arteries

Abstract: The absence of putative pathogenic bacteria in internal mammary arteries, which are known to be affected rarely by atherosclerotic changes, and their presence in a high percentage of atherosclerotic coronary arteries support the concept that periodontal organisms are associated with the development and progression of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
3
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 37 publications
4
112
3
7
Order By: Relevance
“…Other recent studies have suggested that S. mutans migrates to cardiovascular endothelial tissue [24] and binds to extracellular matrix molecules and fibrinogen [25]. Moreover, DNA from periodontal pathogens was highly prevalent in coronary artery atherosclerosis samples taken from patients with coronary artery disease [26]. These findings support the view that infection with oral bacterial species could be a risk factor for coronary heart disease.…”
Section: Discussionsupporting
confidence: 75%
“…Other recent studies have suggested that S. mutans migrates to cardiovascular endothelial tissue [24] and binds to extracellular matrix molecules and fibrinogen [25]. Moreover, DNA from periodontal pathogens was highly prevalent in coronary artery atherosclerosis samples taken from patients with coronary artery disease [26]. These findings support the view that infection with oral bacterial species could be a risk factor for coronary heart disease.…”
Section: Discussionsupporting
confidence: 75%
“…These findings however are relatively new and more research is needed to investigate their contribution to periodontitis and systemic diseases [95].…”
Section: Periodontal Bacteriamentioning
confidence: 99%
“…Usando méto-dos de biología molecular (38), recientemente se identificó una alta prevalencia (60%) de ADN de patóge-nos periodontales dentro de las arterias coronarias con aterosclerosis pero no en las paredes de los vasos mamarios, sugiriendo un papel directo de estos gér-menes en el desarrollo de la aterosclerosis. Además, la periodontitis también modula la estructura del HDL y promueve un perfil lipídico proaterogénico (39).…”
Section: El Amiloide a Sérico Y Su Relación Con Enfermedad Periodontalunclassified